2023
DOI: 10.3389/fpain.2023.1097379
|View full text |Cite
|
Sign up to set email alerts
|

Digital health in pain assessment, diagnosis, and management: Overview and perspectives

Abstract: Managing pain is essential for social, psychological, physical, and economic reasons. It is also a human right with a growing incidence of untreated and under-treated pain globally. Barriers to diagnosing, assessing, treating, and managing pain are complicated, subjective, and driven by patient, healthcare provider, payer, policy, and regulatory challenges. In addition, conventional treatment methods pose their own challenges including the subjectivity of assessment, lack of therapeutic innovation over the las… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
(54 reference statements)
0
10
0
Order By: Relevance
“…Several studies have found promising findings of AI-based pain detection through facial expressions [ 25 ]. ML and AI can use data, whether self-report measures, physiological markers, or medical records, to create algorithms to better understand pain, assess changes to pain, and potentially predict treatment outcomes [ 27 , 28 ]. These technologies can help improve the reliability of pain assessment tools.…”
Section: Incorporation Of Artificial Intelligence For Objective Pain ...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have found promising findings of AI-based pain detection through facial expressions [ 25 ]. ML and AI can use data, whether self-report measures, physiological markers, or medical records, to create algorithms to better understand pain, assess changes to pain, and potentially predict treatment outcomes [ 27 , 28 ]. These technologies can help improve the reliability of pain assessment tools.…”
Section: Incorporation Of Artificial Intelligence For Objective Pain ...mentioning
confidence: 99%
“…AI and ML incorporate large datasets with complex compositions, combining multiple modalities from different sources and allow data sharing to extract information from the data that can be transformed into knowledge about the patient’s experience of pain [ 91 ]. These data can assist clinicians in identifying the underlying mechanisms of pain and offer appropriate treatment strategies [ 27 ]. They can classify pain into nociceptive, neuropathic, or inflammatory pain.…”
Section: Incorporation Of Artificial Intelligence For Objective Pain ...mentioning
confidence: 99%
“…In current clinical settings, patients typically self-report their pain level using the Verbal Rating Scale (VRS), Visual Analogue Scale (VAS), and Numerical Rating Scale (NRS) [19][20][21]. These self-reported pain measurements are subjective and often impractical when patients are not in an alert state or unable to communicate their pain level [22,23]. Infants, toddlers, and adults with communication or cognitive deficits may be unable to convey their pain levels verbally [24].…”
Section: Pain Assessmentmentioning
confidence: 99%
“…Research on complementary therapies such as acupuncture, massage, and mindfulness practices has shown potential benefits in managing pain and improving quality of life. These complementary approaches, when used in conjunction with standard pain management strategies, can contribute to more effective and holistic pain control [18].…”
Section: Introductionmentioning
confidence: 99%